Is business performance of further education colleges improved by entrepreneurial leadership and the adoption of a positive market orientation?: an empirical study of English FE colleges - Flynn, Mark Barry Johnston (2002)
The political role of English further education colleges has been ambiguous for some 20 years, being a nationally funded service administered by local government. In 1993 this role ambiguity was challenged with the incorporation of colleges, accompanied by a shift in the locus of power to national government. Significant cultural change was driven through by an expansionary yet punitive funding regime based on the principles of the free market. In common with other parts of the public sector, this change in orientation has had mixed results. This thesis explores the issues that face the leaders of the modern FE college, approaching the subject from the perspectives of entrepreneurial leadership and market orientation. The sector was dominated by financial instability during the first five years, with the next three being characterised by improving financial health for some colleges and the failure of others. The sector has lost 25 colleges since incorporation through mergers and takeovers. The removal of barriers to competition and the development of rising standards underpinned by audit and inspection have required colleges to adapt to a hostile and turbulent operating environment. A new management paradigm and approach to client orientation has been required to compete and survive in the post incorporation era. The roles of entrepreneurial leadership and market orientation and their impact on business performance have not been widely studied in the UK public sector and the further education sector in particular. The thesis is based on an empirical study of a sample of 250 colleges, representing 60% of English FE colleges. Using quantitative analysis tools, the direction and strength of causal relationships are explored. The financial performance measurement problems typical of public sector are explored using data envelopment analysis and linear structural equations. The thesis concludes with a review of the managerial implications of the study by way of three qualitative case studies and elite interviewing, reconciling theory with the results of the study. The thesis ends with a summary of issues for future research direction.